The Effectiveness of Using Multimedia Content to Increase Twelfth Graders' English-Speaking Performance - Fadilla Davarikha (Universitas Negeri Surabaya, 2024)
This study examines the effectiveness of utilizing multimedia content to improve English-speaking proficiency among twelfth-grade students. The research adopted a quasi-experimental design, involving a sample of 70 twelfth graders from one of the vocational high schools in Surabaya. The experimental group underwent English-speaking sessions utilizing multimedia materials, whereas the control group received conventional instruction. Pre-test and post-test assessments were conducted to gauge speaking proficiency. The analysis revealed a significant disparity between the pre-test mean (69.65) and post-test mean (80.13) scores in the experimental class. Conversely, the control class exhibited a pre-test mean of 65.29, with a slight increase to 70.94 post-test. The results unveiled a noteworthy enhancement in speaking performance among students in the experimental group compared to the control group. These findings suggest that integrating multimedia content into English-speaking instruction can effectively enhance students' speaking abilities in language acquisition. Hypothesis testing confirmed a substantial difference (T-test value > T-table value), underscoring the considerable impact of multimedia.